Tubulin and its prokaryotic homologue FtsZ: a structural and functional comparison. (1st July 2009) - Dyer, Nigel
Microtubules are one of the three primary constituents of the eukaryotic cytoskeleton and are constructed from the protein tubulin. FtsZ is a close structural homologue of tubulin within prokaryotes, and plays an important structural role during cell division. This article compares what is known about the structures that these two homologues are able to form in vivo and in vitro and examines the evidence that the water in the immediate vicinity of the structures, particularly in microtubules, may play an important role in their formation and stability. The article then examines evidence that this hydration layer might help our understanding of how the structures formed by tubulin and FtsZ are stabilised by associated proteins and selected cations. The article then considers recent studies of the charge distribution and dipole moments of tubulin and extends this work to include the electrostatic characteristics of FtsZ. There is then an examination of the ways in which the electrostatic similarities and differences between the two proteins might be related to the similarities and differences in the filamentary structures that they form.